Intermediate-affinity interleukin-2 receptor expression predicts CD56(bright) natural killer cell expansion after daclizumab treatment in the CHOICE study of patients with multiple sclerosis - Sheridan, James P; Zhang, Ying; Riester, Katherine; Tang, Meina T; Efros, Lyubov; Shi, Jia; Harris, Jeffrey; Vexler, Vladimir; Elkins, Jacob S (Multiple sclerosis, 2011)
The objective of this study was to evaluate whether interleukin-2 (IL-2) receptor expression on CD56(bright) natural killer (NK) cells predicted CD56(bright) NK cell expansion and therapeutic response to daclizumab (DAC) in multiple sclerosis (MS). DAC exposure, CD56(bright) NK cell counts, IL-2 receptor alpha (CD25) and beta (CD122) subunits, and new or enlarged lesions on brain MRI were measured in 64 subjects in a pharmacokinetic/pharmacodynamic substudy of the phase 2 CHOICE trial at multiple time points. Peripheral blood mononuclear cell (PBMC) samples were obtained from healthy subjects to assess the relationship among DAC treatment, intermediate affinity IL-2 signaling, and CD56(bright) NK cell expansion. Increased CD56(bright) NK cell counts in DAC/interferon beta (IFNβ)-treated subjects were observed by day 14, the first post-dosing time point (mean [SD] ln{CD56(bright) NK cell count}: DAC high/IFNβ, 2.01 [1.25]; DAC low/IFNβ, 2.29 [1.06]; placebo/IFNβ, 1.01 [1.03]; adjusted p = 0.003), and persisted throughout the treatment period. Higher DAC dose predicted a faster rate of CD56(bright) NK cell expansion (p < 0.001), but individual subjects' increases in CD56(bright) NK cells from baseline levels were only weakly correlated with DAC exposure (r(2) = 0.167). Higher expression of the intermediate-affinity IL-2 receptor subunit (CD122) on CD56(bright) NK cells at baseline predicted fewer new gadolinium-enhanced (Gd+) lesions during the treatment period (1.77 vs. 0.62 adjusted mean new Gd+ lesions during weeks 8-24, lowest vs. highest quartile of percentage CD122(+) CD56(bright) NK cells; p = 0.033) and a greater increase in CD56(bright) NK cell counts at the end of DAC dosing (p = 0.029). CD56(bright) NK cell expansion after DAC treatment appears to reflect individual differences in the capacity for intermediate-affinity IL-2 signaling and could provide a basis for predicting clinical response to DAC in MS.